The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7860/jcdr/2016/18547.7397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Long Term Effect of RV Apical Pacing on Global LV Function by Echocardiography

Abstract: RV-apical pacing induces iatrogenic electrical dyssynchrony which leads to remodeling of LV and produces mechanical dyssynchrony which is responsible for LV dysfunction. Alternate site of RV pacing and/or biventricular pacing should be done to maintain biventricular electrical synchrony which will preserve the LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Similar to the results by Ebert et al [15], our study showed that the deterioration in LVEF was gradual and progressive and more in patients who had baseline LV dysfunction. Our findings were in accordance with the study conducted by Sarkar et al [16] which have shown worsening LV diastolic and systolic functions after pacemaker implantation. Our findings were in accordance with the study by Dwivedi et al [17] which showed that diastolic dysfunction develops as early as first week after pacemaker implantation.…”
Section: Discussionsupporting
confidence: 94%
“…Similar to the results by Ebert et al [15], our study showed that the deterioration in LVEF was gradual and progressive and more in patients who had baseline LV dysfunction. Our findings were in accordance with the study conducted by Sarkar et al [16] which have shown worsening LV diastolic and systolic functions after pacemaker implantation. Our findings were in accordance with the study by Dwivedi et al [17] which showed that diastolic dysfunction develops as early as first week after pacemaker implantation.…”
Section: Discussionsupporting
confidence: 94%
“…The development of pacing induced cardiomyopathy with severe LV impairment before her second pregnancy was an unfortunate, but well-described complication of long-term pacing in the young, which responded to resynchronisation therapy. 7,8 This case highlights the benefit of multidisciplinary teams looking after pregnant women with cardiovascular disease. The ESC guidelines on the management of cardiovascular disease in pregnancy recognise this and emphasise the value of a pregnancy heart team for all women at moderate or high risk of complications during pregnancy.…”
Section: Discussionmentioning
confidence: 94%
“…The development of pacing induced cardiomyopathy with severe LV impairment before her second pregnancy was an unfortunate, but well-described complication of long-term pacing in the young, which responded to resynchronisation therapy. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…In juvenile dogs, prolonged ectopic pacing resulted in CM damage including myofibrillar disarray (Karpawich et al, 1990). Long-term right ventricular apical pacing in adult patients generated electrical dyssynchrony, leading to LV remodeling and dysfunction (Sarkar et al, 2016). Thus, the role of chronic pacing and the underlying cellular and molecular mechanisms affecting maturation remain unknown.…”
Section: Discussionmentioning
confidence: 99%